A marketing plan for the Computerized Index to Philippine Periodical Articles (CIPPA) - Sagun, Karryl Kim A.; Cruz, Edison D. (Quezon City University of the Philippines Diliman, Technology Management Center, 2011)
The Computerized Index to Philippine Periodicals Articles (CIPPA) is an in-house developed product by the Ateneo de Manila University Rizal Library. It was created primarily to serve the needs of the Ateneo community, as many have been clamoring for an easier way of locating publications by Filipinos, or about the Philippines, othewise known as Filipiniana materials. However, a number of local academic institutions have made requests to gain access to the index. This is comprised mostly of smaller institutional and academic libraries which cannot afford to create a database such as CIPPA on their own. After a few years of considering the idea, the Rizal Library opened the database for subscription to other interested parties. CIPPA's main market segments (outside of the Ateneo de Manila University) are comprised of local academic institutions : colleges, universities, and other research-intensive entities. They have been charged for a minimal fee, just enough to cover the maintenance expenses of delivering the service to them. The cost of creating and developing the product is shouldered fully by the Rizal Library.
During the last three years, there has been a reported decline in the number of subscribers to the database, according to the sales records of the Rizal Library. The Rizal Library Director's Secretary asked a couple of the discontinuing subscribers, wanting to find out the reason behind this trend, and found out that the suspension of subscription is due to the lack of full text access of subscribers to the index. The CIPPA, in itself, acts only as a directional tool which points the user to the location of his query. This is also the main issue of the internal customers of the CIPPA (members of the Ateneo community). Databases that they have been using are capable of providing not just the index and the abstract, but also the full text articles of the materials. This has been a problem posed in the development as well as the marketing of the CIPPA.
Another issue raised is the vision to make CIPPA a self-sustaining project by increasing revenue and/or decreasing expenditures in operations and maintenance. CIPPA is being offered by the Rizal Library through B2B (business to business) means which entails having to directly market and sell the product to the customers (other academic institutions, in most cases). This means that the Rizal Library carries the burden, financial or otherwise, of having to promote the database to the various entities belonging to its main target market segment. Another concern here, on the other hand, is that CIPPA was not created as a for-profit product. In fact, revenue or no revenue, the Rizal Library would still create the database because it is an integral part of its service to its main clients, the members of the Ateneo community.
How does one calculate the return on investment (ROI) for the CIPPA? This is also one of the questions posed in the conduct of this project. Libraries are nonprofit organizations, and in addition to that, it is very difficult to measure the ROI in such institutions as they come, more often that not, in non-monetary forms. The Rizal Library measures ROI in most projects by the degree of improvement in the research and academic output of the University, after the project has been materialized. This, however, is a very complicated process, with many factors which must be considered before arriving at a conclusion. For the purposes of this project, the author has decided to not include the marketing ROI in monetary terms, but in the increase in the scope of CIPPA. This, in her opinion, would be enough metrics as CIPPA is a product created for service, not for profit. Thus, in the spending of money, if the extent of service of the product has been amplified, would entail a good measure and indication of success for the project.
Based on Porter's 5 generic strategies, the CIPPA belongs to the low-cost, low differentiation quadrant. Compared to its foreign counterparts, the price that CIPPA is being offered is a very insignificant amount. The RIzal Library, in the pricing of the product, wanted to maintain the subscription costs to a minimum, so that more institutions may be able to benefit from its services. However, the strategy has also been impeding its growth, as it is only marketed (passively) to academic institutions which pick up the telephone and call the Rizal Library. As of date, no aggressive strategy has been implemented to broaden the scope of subscribers to the database. Thus, it is recommended in this plan that the strategy be evaluated and changed as the current strategy is not able to exploit the value of the database.
Initially, the marketing of CIPPA was planned to be outsourced to a middleman. This middleman would be an educational software vendor in the Philippines which would market the product and collect a certain percentage of the proceeds, based on the number of units sold (or in this case, the number of new subscribers to the database). However, in an intervew with the Reference & Information Services Head of the Rizal Library, Mr. Fernan R. Dizon, it was brought up that this strategy would make the CIPPA acquire more monetary deficits-thus, would bring more harm than good to the product. After careful consideration, the author decided to integrate his suggestion of marketing the product in-house, and providing full-text access to selected materials which were available in open access or in public domain through persistent links. This would pose as an efficient solution to the decline of subscribers due to the lack of full-text access, by giving them what they were asking for. In effect, this would also improve the service of CIPPA to its main target market : the members of the Ateneo community.
In partial fulfillment of the requirements of TM 299
Thesis
Keywords: Marketing research; Indexes